Establishing the effect of decreased power intensity of self-oscillatory grinding in a tumbling mill when the crushed material content in the intra-chamber fill is reduced - Deineka, Kateryna; Naumenko, Yuriy (Eastern-European Journal of Enterprise Technologies, 2020)
The influence of the content of crushed material in the intra-chamber grinding fill on the efficiency of the self-oscillatory grinding process in the tumbling mill was assessed. A dynamic effect of a significant decrease in self-oscillatory action of the two-fraction fill of the rotary chamber with an increase in the content of fine fraction was revealed by the method of visual analysis of motion patterns. A decrease in values of the following inertial fill parameters was established: maximum dilatancy υmax, the relative amplitude of self-oscillations ψRυ and a maximum share of the active part κfam max with an increase in the degree of filling the gaps between particles of the coarse fraction κmbgr. A decrease in the generalized complex degree of dynamic activation Ka was also established. The effect is due to the strengthening of the cohesive properties of the incoherent coarse fraction under the influence of the fine fraction. There was a decrease in by 29 % for υmax, by 7 % for ψRυ, 2.9 times for κfam max and 4.2 times for Ka with an increase in κmbgr from 0 to 1 at the degree of filling the chamber with the fill κbr=0.45. Technological effect of a significant decrease in specific energy intensity and an increase in productivity of the innovative self-oscillatory grinding process in comparison with characteristics of the conventional steady-state process at a decrease in the content of crushed material in the fill was established. A process of milling cement clinker with grinding bodies at relative size of 0.026 and κbr=0.45 was considered. A decrease in specific energy intensity by 27 % at κmbgr=1, by 38 % at κmbgr=0.5625 and by 44 % at κmbgr=0 was found. An increase in relative productivity by 7 % at κmbgr=1, by 26 % at κmbgr=0.5625 and by 39 % at κmbgr=0.125 was established. The established effects will make it possible to forecast rational parameters of the self-oscillatory grinding process in a tumbling mill at the variation of the content of the crushed material in the fill